Bimbingan teknis pelaporan dana kampanye berdasarkan Akuntansi Dana Kampanye PKPU 24 tahun 2018 - Samirah Dunakhir; Nur Afiah; Warka Syachbrani (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
This is Training for Political Party personnel. This training aims to socialized about cost of campaign in Makassar.Training based on the Election Commission Regulation (PKPU) Number 24 of 2018 regarding Election Campaign Fundsrequires that every use of campaign funds be audited by a Public Accountant. This Community Partnership Program ProposalTeam has a background in Financial Accounting and Public Sector Accounting. This background is very suitable and supportsthe implementation of the proposed program topic. Meanwhile, the budgeted funds for implementing this program are sourcedfrom PNBP Universitas Negeri Makassar with an implementation period of eight months. Outputs generated through thisprogram include: publication in print / online media; increasing the competitiveness of human resources; increase in theapplication of science and technology.